ATTITUDINAL DISPOSITION OF SECONDARY SCHOOL STUDENTS TOWARDS READING COMPREHENSION IN SOUTH - WEST STATES OF NIGERIA - Adekola, Oluwakemi B. (Sokoto Educational Review, 2020)
The study examined the attitudinal disposition of Secondary School students to Reading Comprehension in South – West States of Nigeria. One hundred and fifty Senior Secondary School 2 students from thirty schools were sampled. A self-designed questionnaire was used to collect data, which was analyzed using percentages. The findings showed that the parental educational background contributes towards the students’ performance in reading comprehension. In addition, the parental environment plays a significant role in facilitating the reading of the children. Based on the findings it was recommended that the teachers, parents and school authority should provide solutions to the factors that hinder effective reading of the students.